Electrolytes for Dual‐Carbon Batteries. Issue 10 (26th March 2019) - Jiang, Xiaoyu; Luo, Laibing; Zhong, Faping; Feng, Xiangming; Chen, Weihua; Ai, Xinping; Yang, Hanxi; Cao, Yuliang
Abstract: Dual‐carbon batteries (DCBs) are a promising candidate for smart grid applications, owing to their low cost, high power capability, and environmentally friendly benefits. As an essential component of DCBs, electrolytes not only act as a medium for ion migration during the running of the battery, but also provide active ions to be intercalated into carbon electrodes, exerting significant impacts on the electrochemical performance and safety of the DCB. In this Review, we discuss recent progress in electrolyte research for DCBs, including conventional liquid electrolytes, highly concentrated electrolytes, and gel polymer electrolytes, with a focus on their stability and compatibility with carbon electrodes. Finally, we present perspectives on the current limitations and future research directions of electrolytes for DCBs. Some recommendations for battery evaluation are also offered. Abstract : Time to dual : Recent progress in dual‐carbon battery electrolytes are comprehensively reviewed with a focus on their stability and compatibility with carbon electrodes. The Review also presents perspectives on the current limitations and future research directions of electrolytes for dual‐carbon batteries.